Gas‐aerosol partitioning of ammonia in biomass burning plumes: Implications for the interpretation of spaceborne observations of ammonia and the radiative forcing of ammonium nitrate. Issue 15 (14th August 2017) - Paulot, F.; Paynter, D.; Ginoux, P.; Naik, V.; Whitburn, S.; Van Damme, M.; Clarisse, L.; Coheur, P.‐F.; Horowitz, L. W.
Abstract: Satellite‐derived enhancement ratios of NH3 relative to CO column burden ( ER NH 3 / CO ) in fires over Alaska, the Amazon, and South Equatorial Africa are 35, 45, and 70% lower than the corresponding ratio of their emissions factors ( EF NH 3 / CO ) from biomass burning derived from in situ observations. Simulations performed using the Geophysical Fluid Dynamics Laboratory AM3 global chemistry‐climate model show that these regional differences may not entirely stem from an overestimate of NH3 emissions but rather from changes in the gas‐aerosol partitioning of NH3 to NH 4 + . Differences between ER NH 3 / CO and EF NH 3 / CO are largest in regions where EF NO x / NH 3 is high, consistent with the production of NH4 NO3 . Biomass burning is estimated to contribute 11–23% of the global burden and direct radiative effect (DRE) of NH4 NO3 (−15 to −28 mW m −2 ), despite accounting for less than 6% of the global source of NH3 . Production of NH4 NO3 is largely concentrated over the Amazon and South Equatorial Africa, where its DRE can reach −1.9 W m −2 during the biomass burning season. Key Points: NH3 gas‐to‐aerosol partitioning induces regional differences between NH3 emission factors derived from in situ and satellite observations Greatest partitioning is over large savanna and tropical forest fires, where NO emissions exceed those of NH3, promoting NH4 NO3 production Fires can contribute over 20% of the NH4 NO3 burden and associated radiative effect despite accounting for less than 6% of NH3 emissions